Reconstitution of T Cell Proliferation under Arginine Limitation: Activated Human T Cells Take Up Citrulline via L-Type Amino Acid Transporter 1 and Use It to Regenerate Arginine after Induction of Argininosuccinate Synthase Expression - Werner, Anke; Koschke, Miriam; Leuchtner, Nadine; Luckner-Minden, Claudia; Habermeier, Alice; Rupp, Johanna; Heinrich, Christin; Conradi, Roland; Closs, Ellen I.; Munder, Markus (Frontiers in Immunology, 2017)
In the tumor microenvironment, arginine is metabolized by arginase-expressing myeloid cells. This arginine depletion profoundly inhibits T cell functions and is crucially involved in tumor-induced immunosuppression. Reconstitution of adaptive immune functions in the context of arginase-mediated tumor immune escape is a promising therapeutic strategy to boost the immunological anti-tumor response. Arginine can be recycled in certain mammalian tissues from citrulline via argininosuccinate in a two-step enzymatic process involving the enzymes argininosuccinate synthase (ASS) and argininosuccinate lyase (ASL). Here we demonstrate that anti-CD3/anti-CD28-activated human primary CD4+ and CD8+ T cells upregulate ASS expression in response to low extracellular arginine concentrations, while ASL is expressed constitutively. ASS expression peaked under moderate arginine restriction (20 μM), but no relevant induction was detectable in the complete absence of extracellular arginine. The upregulated ASS correlated with a reconstitution of T cell proliferation upon supplementation of citrulline, while the suppressed production of IFN-γ was refractory to citrulline substitution. In contrast, argininosuccinate reconstituted proliferation and cytokine synthesis even in the complete absence of arginine. By direct quantification of intracellular metabolites we show that activated primary human T cells import citrulline but only metabolize it further to argininosuccinate and arginine when ASS is expressed in the context of low amounts of extracellular arginine. We then clarify that citrulline transport is largely mediated by the L-type amino acid transporter 1 (LAT1), induced upon human T cell activation. Upon siRNA-mediated knockdown of LAT1, activated T cells lost the ability to import citrulline. These data underline the potential of citrulline substitution as a promising pharmacological way to treat immunosuppression in settings of arginine deprivation.